The Balance Between Choice, Initial Prosthetic Valve Selection, and Future Transcatheter Success: A Patient-Centered Strategic Perspective - Caio Cesar Cardoso; José de Lima Oliveira Jr; SO Cardoso (Journal of Clinical Cardiology, 2026)
The emergence of transcatheter valve-in-valve (ViV) procedures has fundamentally changed the management of bioprosthetic valve degeneration, providing a less invasive alternative to high-risk surgical reoperation. However, the long-term clinical success of future transcatheter interventions is largely predetermined at the time of the initial surgical valve replacement. This commentary discusses how initial prosthetic choice—type, design, and intraoperative sizing—impacts the patient’s lifelong therapeutic journey. While contemporary consensus guidelines present comprehensive frameworks balancing patient age, desire for pregnancy, frailty, and contraindications to oral anticoagulation, we emphasize an important geometric link. In patients with small annular anatomy, where the size of the implanted heart valve prosthesis is already borderline for severe prosthesis-patient mismatch (PPM), mechanical valves remain a reasonable, evidence-based alternative to maintain long-term hemodynamic stability when anticoagulation is feasible and tolerated. Conversely, larger rings foster a bioprosthetic approach focused on future transcatheter horizons. By integrating hydrodynamic evidence with international clinical guidelines, we present a conceptual strategic framework to guide modern heart teams.